Transforming Rice Cultivation in the Hilly Regions of Bangladesh: A Story of Resilience and Innovation - Habib, Muhammad Ashraful; Nayak, Swati; Nuruzzaman; Islam, Saidul (Rice Today, International Rice Research Institute, 2025)
The Chittagong Hill Tracts (CHT) in southeastern Bangladesh is a low-productive hilly agricultural region, where rice cultivation is severely hampered due to inaccessible topography, limited irrigation facilities, low soil fertility, and limited availability of improved rice varieties. To address these challenges, IRRI and Bangladesh Rice Research Institute (BRRI) conducted farmer-led Head-to-Head Adaptive Trials in Khagrachhari and Rangamati districts to select rice varieties suitable for the TLaMF-I(Transplanted, late duration, medium slender-irrigated) market segment. Among the tested varieties, BRRI Dhan88 and BRRI Dhan100 consistently show superior yield compared to local varieties BRRI Dhan28 and benchmark varieties BRRI Dhan74, where the yield increase reaches a maximum of 24.64%. These varieties exhibit high yield stability, tolerance and improved feed quality in water-less environments. Participatory testing of male and female farmers has strengthened variety, seed dispersal and local entrepreneurship. The expansion of BRRI Dhan88 and BRRI Dhan100 is significantly improving productivity, food security, farmer income, and agricultural sustainability in the hilly regions.